The impact of business improvement district proximity on street block robbery counts - Clutter, Jeffrey E. (Crime & delinquency, 2019)
This study examined the impact of business improvement districts (BIDs) on street block robbery counts in Cincinnati, OH. The relationships among BIDs (as well as other relevant control measures) and street block robbery counts were then examined using negative binomial regression models. Results showed that BIDs played an important role in the spatial patterning of robbery at the street block level. Street blocks within BIDs experienced higher street robbery counts even after controlling for street network betweenness and the presence of potentially criminogenic places within and around BIDs. Although previous research suggests BID implementation leads to crime reductions, the present study shows BIDs still provide ample opportunities for criminal activity as one component of the environmental backcloth.